PENGARUH KESIAPAN SEKOLAH TERHADAP DUKUNGAN SOSIAL ORANG TUA DALAM IMPLEMENTASI KEBIJAKAN INKLUSI DI SURABAYA - Fawwazzaidan Dian Nafis; Ima Fitri Sholichah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The implementation of inclusive education in elementary schools still faces various challenges, particularly regarding school readiness in providing curriculum, human resources, facilities and infrastructure, and building parental trust. Limited school readiness may influence parents’ social support for the implementation of inclusive education. This study aimed to examine the effect of school readiness on parents’ social support in implementing inclusive education policy in public elementary schools in Surabaya. This study used a quantitative approach with an associative design. The sample consisted of 143 parents whose children attended public elementary schools implementing inclusive education in Surabaya, selected using accidental sampling. The research instruments consisted of a school readiness scale covering curriculum, human resources, and facilities and infrastructure, and a parental social support scale covering emotional and instrumental support. The data were analyzed using simple linear regression with the assistance of JASP software. The results showed that school readiness had a positive and significant effect on parents’ social support, B = 0.315, β = 0.534, t = 7.506, p < 0.001. The R² value of 0.285 indicated that school readiness explained 28.5% of the variance in parents’ social support, while the remaining 71.5% was influenced by other factors outside the research model. This study concludes that the higher the level of school readiness, the higher the level of parents’ social support in implementing inclusive education. The implication of this study emphasizes the importance of strengthening school capacity, providing teacher training, developing inclusive facilities, and establishing effective communication with parents to support the successful implementation of inclusive education. ABSTRAK Implementasi pendidikan inklusi di sekolah dasar masih menghadapi berbagai kendala, terutama terkait kesiapan sekolah dalam menyediakan kurikulum, sumber daya manusia, sarana-prasarana, serta membangun kepercayaan orang tua. Kesiapan sekolah yang belum optimal dapat memengaruhi dukungan sosial orang tua terhadap pelaksanaan pendidikan inklusi. Penelitian ini bertujuan untuk mengetahui pengaruh kesiapan sekolah terhadap dukungan sosial orang tua dalam implementasi kebijakan inklusi di sekolah dasar negeri di Surabaya. Penelitian ini menggunakan pendekatan kuantitatif dengan desain asosiatif. Sampel penelitian berjumlah 143 orang tua yang memiliki anak di sekolah dasar negeri penyelenggara pendidikan inklusi di Surabaya dan dipilih menggunakan teknik accidental sampling. Instrumen penelitian terdiri atas skala kesiapan sekolah yang mencakup aspek kurikulum, sumber daya manusia, serta sarana dan prasarana, serta skala dukungan sosial orang tua yang mencakup dukungan emosional dan instrumental. Data dianalisis menggunakan regresi linier sederhana dengan bantuan perangkat lunak JASP. Hasil penelitian menunjukkan bahwa kesiapan sekolah berpengaruh positif dan signifikan terhadap dukungan sosial orang tua, B = 0,315, β = 0,534, t = 7,506, p < 0,001. Nilai R² = 0,285 menunjukkan bahwa kesiapan sekolah menjelaskan 28,5% variasi dukungan sosial orang tua, sedangkan 71,5% sisanya dipengaruhi oleh faktor lain di luar model penelitian. Penelitian ini menyimpulkan bahwa semakin tinggi kesiapan sekolah, semakin tinggi pula dukungan sosial orang tua dalam implementasi pendidikan inklusi. Implikasi penelitian ini menekankan pentingnya penguatan kapasitas sekolah, pelatihan guru, penyediaan fasilitas inklusif, dan komunikasi efektif dengan orang tua untuk mendukung keberhasilan pendidikan inklusi.